Application of Total Quality Services to Increase Non-Formal Education Institution Capacity in Kampung Inggris Kediri - Rinto Alexandro (Center of Language and Cultural Studies, 2020)
The objective of this study is to obtain a fixed model that can be applied in the framework of capacity building of course institutions through meeting national standards for non-formal education, accreditation registration, and the application of total quality service. This research method is action research ranging from the formation of teams per area & Need assessment, data processing of the needs assessment survey, socialization and training, facilitation of 20-course institutions to be registered for institutional accreditation to National Accreditation Board for Early Childhood Education and Non-Formal Education (BAN-PAUD-PNF), assistance to thin management institutions in prepare accreditation and implementation of TQS, explore cooperation with BAN-PAUD-PNF in Jakarta. Based on the results of data analysis it can be concluded: 1) to increase the capacity of course institutions it is necessary to improve quality through the accreditation of institutions from official state institutions, ISOs, and from the application of total quality service management (TQS). Through institutional accreditation, it will be able to increase public confidence in the existing course institutions. Likewise, with ISO, it will be able to increase public confidence, that the institution has implemented good management.